Activation of the Thiazide-Sensitive Sodium-Chloride Cotransporter by Beta3-Adrenoreceptor in the Distal Convoluted Tubule - Milano, Serena; Carmosino, Monica; Gerbino, Andrea; Saponara, Ilenia; Lapi, Dominga; Dal Monte, Massimo; Bagnoli, Paola; Svelto, Maria; Procino, Giuseppe (Frontiers in Physiology, 2021)
We previously showed that the beta-3 adrenergic receptor (BAR3) is expressed in most segments of the nephron where its agonism promotes a potent antidiuretic effect. We localized BAR3 in distal convolute tubule (DCT) cells expressing the thiazide-sensitive sodium-chloride cotransporter (NCC). Aim of this study is to investigate the possible functional role of BAR3 on NCC modulation in DCT cells. Here we found that, in mice, the knockout of BAR3 was paralleled by a significant attenuation of NCC phosphorylation and reduced expression and activation of SPAK, the main kinase involved in NCC activation. Conversely, in BAR1/2 knockout mice we found reduced NCC abundance with no changes in the phosphorilation state of NCC and SPAK. Moreover, selective BAR3 agonism promotes both SPAK and NCC activation in wild-type mouse kidney slices. In conclusion our findings suggest a novel role for BAR3 in the regulation of NCC in DCT.